Dvorak's guide to PC telecommunications. - Dvorak, John C. (McGraw-Hill, Inc., 1990)
"You'll find out all about modems, how they work and how to best use them; tips and tricks for linking two remote computers; and how to establish an office at home. You'll also learn about each of the major electronic mail systems and bulletin board services-what they are and how they can work for you. The authors review the most popular telecommunications packages, the on-line services, obscure databases everything you want to know about." (Copied from the paste).